2014
DOI: 10.1111/ijlh.12235
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of coagulation test results under direct oral anticoagulants

Abstract: Summary Diagnostic of global coagulation parameters is part of the daily clinical routine practice in conservative as well in operative disciplines. The correct interpretation of in vitro test results in context to the ex vivo influence of anticoagulant drugs and the in vivo hemostatic system of the individual patient is dependent on the doctors clinical and laboratory experience. This article shortly reviews the laboratory interference of oral anticoagulants including the target‐specific inhibitors dabigatran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…was measurable. This effect may occur with other APTT-based factor assays, including factor IX and factor XI activity assays [41,42]. Therefore, APTT-based screening tests, mixing studies, factor activity analysis, and even Bethesda assays may yield spurious results in the presence of dabigatran, leading to a false impression of either a factor deficiency, or the presence of a specific factor inhibitor [29,41].…”
Section: Dabigatran -Interference In Specialty Coagulation Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…was measurable. This effect may occur with other APTT-based factor assays, including factor IX and factor XI activity assays [41,42]. Therefore, APTT-based screening tests, mixing studies, factor activity analysis, and even Bethesda assays may yield spurious results in the presence of dabigatran, leading to a false impression of either a factor deficiency, or the presence of a specific factor inhibitor [29,41].…”
Section: Dabigatran -Interference In Specialty Coagulation Assaysmentioning
confidence: 99%
“…Dabigatran may cause false positive lupus anticoagulant (LA) results but will not affect ELISA-based antiphospholipid assays [41,43]. Chromogenic or latex immunoassays including plasminogen activity, quantitative D-dimer, free protein S antigen, chromogenic protein C activity, von Willebrand factor antigen, and von Willebrand factor activity (ristocetin cofactor), are not affected by the presence of dabigatran [41][42][43]. Laboratories with limited access to patient information (eg, reference laboratories) may require a mechanism (e.g.…”
Section: Dabigatran -Interference In Specialty Coagulation Assaysmentioning
confidence: 99%
“…Therefore, these assays, for example, measures of antithrombin, protein C, or protein S activity, APC resistance, and lupus anticoagulant testing, should not be performed in patients on these drugs. 23,[32][33][34] False-positive testing for lupus anticoagulants, even with a positive phospholipid correction step, have been reported in patients on each of these drugs. 34 Measures of antigen levels or DNA-based assays will not be affected by these drugs.…”
Section: Influence Of Tsoacs On Other Coagulation Assaysmentioning
confidence: 99%
“…16,35 Fibrinogen measured using a prothrombin-based method may be artifactually elevated by all 3 drugs, the extent depending on the reagent used. 33 Individual clotting factor assays may also be affected. This will depend in part on the reagent and methodology used.…”
Section: Influence Of Tsoacs On Other Coagulation Assaysmentioning
confidence: 99%
“…We confirmed that to reliably evaluate LA in VTE patients on rivaroxaban, blood should be taken at least 24 h after the last drug administration [69]. It has been recommended that the LA testing should be performed 2-3 days after the last dose of DOACs [71].…”
Section: Effect Of Doacs On Results Of Thrombophilia Testing Lupus Anmentioning
confidence: 59%